Nosocomial Sepsis in Neonatal Intensive Care: Inevitable or Preventable? - Bersani, I.; Speer, C. P. (Zeitschrift für Geburtshilfe und Neonatologie, 2012)
Very low birth weight (VLBW) infants are at high risk to develop a neonatal nosocomial sepsis. The incidence of neonatal nosocomial, late-onset sepsis (LOS) is about 20–30%, but a rate of up to 43% has been reported among neonates with a birth weight of 400–750 g. Preventive and treatment strategies for neonatal sepsis in VLBW infants are aiming to enhance the infant’s host defence mechanisms. Neonatal immunodeficiencies include quantitative and qualitative deficits in phagocytes, complement components, and immunoglobulins. A considerable number of immune strategies has been investigated in carefully designed multicentre trials. These include exchange transfusion, neutrophil transfusion, hematopoietic growth factors such as granulocyte-macrophage colony-stimulating factor (GM-CSF) and granulocyte colony-stimulating factor (G-CSF), intravenous immunoglobulins (IVIG), and others. Since none of these interventions was able to reduce the mortality rate of immature preterm infants, the current evidence does not support the use of any of the immune strategies for prevention or treatment of neonatal sepsis. Decreasing the burden of intensive care and following strict hygiene programs at NICUs may be the most promising current strategies to minimise nosocomial infection.
Keywords: granulocyte colony-stimulating factor; granulocyte-macrophage colony-stimulating factor; intravenous immunoglobulins; hygienic strategies; neonates; nosocomial sepsis